Assessing the efficiency of the effect of innovations on the development of grain processing enterprises - Yessakhmetova, Lyailya; Dzholdasbaeva, Gulnar; Saurukova, Ainura; Sauranova, Meruert; Alibekova, Aigul (Eastern-European Journal of Enterprise Technologies, 2024)
This study evaluates the impact of the introduction of deep grain processing on the development of grain processing enterprises. The main problems of processing grain crops in the Republic of Kazakhstan have been considered. The need to assess the impact of the innovative process of enterprise development was outlined. The research was carried out in the North-Kazakhstan region; the object of the study was the grain processing industries in the North-Kazakhstan region. The results show the following: 1) total cost savings when expanding the level of gluten consumption (up to 3 % by weight of the volume of flour consumed) will save USD 18.5 billion. The savings are due to the significant improvement in the baking properties of the flour when adding 1−3 % gluten to the level of the highest quality wheat flour. At the same time, due to the manufacturability of the process and the use of the lowest quality raw materials, the unit cost of gluten in terms of protein is lower than the price of high-quality wheat necessary for baking; 2) in the processing of starch and amino acids, grain starch is the main product of world trade among all goods of the grain processing industry, and gluten ranks only second in terms of world imports. The share of issued patents in the area of starch production is also leading among the sectors of deep grain processing; 3) the implementation of the developed project for deep processing of grain in Northern Kazakhstan could significantly improve the indicators of innovative development of the country: the increase in innovative products of the manufacturing industry in the country as a whole would be 19.1 %. The growth of non-resource exports would equal 1.5 %. The annual increase in the enterprise’s revenue could be about USD 0.47 per USD 1 of investment costs compared to the base scenario for the sale of unprocessed wheat. The scope of practical application of the results extends to the grain industry. The project has a significantly wider range of manufactured products and is focused on the markets of neighboring countries, which could reduce export risks to a minimum and provide stable demand for the company’s products